2015
DOI: 10.1093/dnares/dsv018
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome and gene expression analyses ofAsaia bogorensisreveal unique responses to culture with mammalian cells as a potential opportunistic human pathogen

Abstract: Asaia bogorensis, a member of acetic acid bacteria (AAB), is an aerobic bacterium isolated from flowers and fruits, as well as an opportunistic pathogen that causes human peritonitis and bacteraemia. Here, we determined the complete genomic sequence of the As. bogorensis type strain NBRC 16594, and conducted comparative analyses of gene expression under different conditions of co-culture with mammalian cells and standard AAB culture. The genome of As. bogorensis contained 2,758 protein-coding genes within a ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 63 publications
(88 reference statements)
2
21
1
Order By: Relevance
“… 6 GC skew analysis to anchor potential origin and terminator for chromosome replication did not show obvious skew shift. This is different from those bacteria whose chromosomal replication origin and terminator could be clearly identified, 9 , 25 but is similar to other cyanobacterial genomes, suggesting the occurrence of potential chromosomal rearrangements, sequence duplications and lateral gene transfer (LGT) events, 26 because the bias of nucleotide compositions between leading and lagging strands were disrupted. In addition, mapping Illumina short reads back to the genome resulted in 99.6% of the total reads uniquely aligned to the assembly and 98.4% paired-end reads represented correct orientation and distance, which was indicative of the high credibility of the assembled genome.…”
Section: Resultscontrasting
confidence: 78%
“… 6 GC skew analysis to anchor potential origin and terminator for chromosome replication did not show obvious skew shift. This is different from those bacteria whose chromosomal replication origin and terminator could be clearly identified, 9 , 25 but is similar to other cyanobacterial genomes, suggesting the occurrence of potential chromosomal rearrangements, sequence duplications and lateral gene transfer (LGT) events, 26 because the bias of nucleotide compositions between leading and lagging strands were disrupted. In addition, mapping Illumina short reads back to the genome resulted in 99.6% of the total reads uniquely aligned to the assembly and 98.4% paired-end reads represented correct orientation and distance, which was indicative of the high credibility of the assembled genome.…”
Section: Resultscontrasting
confidence: 78%
“…In studies conducted by Kawaii et al (2015) it was found that bacterium Asaia bogorensis has an operon with genes that were homologous to rhodopsin and beta-carotene 15,15′-monooxygenase—participating in the synthesis of phytofluene and neurosporene ( Appendix A Figure A2 ) [ 20 ]. Our results showed that tested strains of A. bogorensis did not accumulate the first compound, but can produce neurosporene.…”
Section: Resultsmentioning
confidence: 99%
“…It was noted that in the case of Escherichia coli , low oxygen concentrations increase the level of menaquinones, and therefore, reduce the amount of ubiquinones [ 42 ]. On the other hand, Kawai et al (2015), in the study on Asaia bogorensis , found that A. bogorensis , like Escherichia coli , contains cyd genes (encoding cytochrome d oxidase), whose expression is upgraded under oxygen limited conditions [ 20 ]. The presence of MC-7 and MC-8, as well as expression of cyd genes, is important, due to the fact that Asaia lannensis and Asaia bogorensis contaminate functional beverages containing low levels of oxygen.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations